Neuropathological and behavioral features of an APP/PS1/MAPT (6xTg) transgenic model of Alzheimer's disease - Tag, Sung Hyun; Kim, Baeksun; Bae, Jinhee; Chang, Keun-A; Im, Heh-In (BioMed Central, 2022)
Alzheimer's disease is associated with various brain dysfunctions, including memory impairment, neuronal loss, astrocyte activation, amyloid-beta plaques, and neurofibrillary tangles. Transgenic animal models of Alzheimer's disease have proven to be invaluable for the basic research of Alzheimer's disease. However, Alzheimer's disease mouse models developed so far do not fully recapitulate the pathological and behavioral features reminiscent of Alzheimer's disease in humans. Here, we investigated the neurobehavioral sequelae in the novel 6xTg mouse model of Alzheimer's disease, which was developed by incorporating human tau containing P301L mutation in the widely used 5xFAD mouse model of Alzheimer's disease. At 11-months-old, 6xTg mice displayed the core pathological processes found in Alzheimer's disease, including accumulation of amyloid-beta plaque, extensive neuronal loss, elevated level of astrocyte activation, and abnormal tau phosphorylation in the brain. At 9 to 11-months-old, 6xTg mice exhibited both cognitive and non-cognitive behavioral impairments relevant to Alzheimer's disease, including memory loss, hyperlocomotion, anxiety-like behavior, depression-like behavior, and reduced sensorimotor gating. Our data suggest that the aged 6xTg mouse model of Alzheimer's disease presents pathological and cognitive-behavioral features reminiscent of Alzheimer's disease in humans. Thus, the 6xTg mouse model of Alzheimer's disease may be a valuable model for studying Alzheimer's disease-relevant non-cognitive behaviors.